The two-digit revolution enhancing writing fluency, reading readiness, and cognitive development through cursive handwriting instruction - Batan, Celia M. (Tahiko Books, 2018)
"For generations, American school children were taught to write in joined letters. Current educational policies have eliminated this essential skill from the curriculum; in many school districts, children are no longer taught to read or write in cursive. With installation of screens and keyboards in the classroom, is cursive handwriting an outdated technology, irrelevant in the modern digital world? This book explores two major questions: 1. Why should we care about teaching cursive handwriting to our children?2. What are possibly lost to children’s cognitive development when thoughts are typed on the screen instead of written on paper in long hand? If these questions cross your mind even in a most fleeting way, this book invites you to read about a wide cross-reference of independent research studies on brain activity and the hand as it holds a writing implement to create letter forms, connecting them to form words. It presents a compelling case for the reinstatement of cursive instruction even as today’s children aim for proficiency in keyboarding. The author, Celia M. Batan, highlights studies that give decision-makers in public education pause: keyboarding skills do not replace hand-writing skills. While keyboarding is an undeniably important part of the future, evidence suggest that it does not provide the benefits that cursive handwriting does. “[Cursive handwriting] shapes the executive functions of the brain for successful academic performance while enhancing creative and critical thinking practices required for meaningful interpretations of what we see. Even more compelling is how handwriting instruction influences neuroplasticity of the brain and contributes to character development and psychological healing”. This book details the connections between the practice of writing by hand and the development of brain executive functions, made by neuroscientists, educators, cognitive scientists, physiologists, occupational therapists, art therapists, graphologists, and psychologists . It is about developing foundations for 'fluid intelligence'— that is, handling of situations with self-regulation-- through continued practice in penmanship K-12. It is beyond ‘beautiful handwriting’ that cursive writing is most commonly remembered for. In fact, it details how the practice of joining letters is an unrecognized vehicle for achieving objectives in State standards for reading, language arts, and STEM subjects. Drawing on studies from diverse fields, Ms. Batan reveals how cursive makes significant contributions to overall cognitive development in early childhood, reading comprehension, writing fluency, improved scores in spelling and syntax- all leading to success in academic and career tracks for 21st century economies, which require skills that a visionary aptly defines: to develop "better ideas to solve more difficult problems". Appendices offer a comparison of penmanship samples of students in the USA and Asia: K-12 and adult education. They also invite educators to consider teachers’ ideas on how to incorporate cursive instruction in daily classroom activities for K-5 grade levels. The author prescribes hand-writing thoughts, outlines, and drafts, then typing for word processing functions: storage, retrieval, layout, and printing copies.With Ms. Batan's reminder that 2019 kindergarteners are the workforce for the year 2036, the book is worth your consideration. At this publication, 15 States have returned to cursive instruction in the primary grades."